Antibiotic resistance of Escherichia coli isolated from broilers sold at live bird markets in Chattogram, Bangladesh - Sarker, Md Samun; Mannan, Md Shahriar; Ali, Md Younus; Bayzid, Md; Ahad, Abdul; Bupasha, Zamila Bueaza (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The present study was carried out to appraise the antibiotic resistance and to detect some of the target resistant genes in Escherichia coli (E. coli) isolated from apparently healthy broilers. Materials and Methods: Cloacal swab samples (n = 60) were collected from apparently healthy broilers (n = 60) sold at two different live bird markets (LBMs) of Chattogram, Bangladesh. Isolation and identification of the Escherichia coli was done by the following standard bacteriological techniques followed by biochemical tests. The antibiotic susceptibility of E. coli isolates was determined by the disk diffusion method. The antibiotic resistant genes were detected by polymerase chain reaction (PCR) using specific primers. Results: The overall prevalence of E. coli in broilers was 61.67% (n = 37/60) (95% CI = 49–72.93). The antibiogram study showed that the isolates were 100% resistant to ampicillin and tetracycline followed by sulfomethoxazole-trimethoprim (94.59%, n = 35/37) and nalidixic acid (91.89%, n = 34/37). To the contrary, 56.76% (n = 21/37) isolates were sensitive to both ceftriaxone and gentamicin followed by colistin (48.65%, n = 18/37). All of E. coli isolates were multidrug resistant (MDR) and carried blaTEM, tetA, and Sul2 genes. Conclusion: The presence of MDR genes in E. coli isolates in broilers could pose a serious public health threat. J. Adv. Vet. Anim. Res., 6(3): 272-277, September 2019